2021
DOI: 10.1002/jnm.2967
|View full text |Cite
|
Sign up to set email alerts
|

DC and RF/analog parameters in Ge‐source split drain‐ZHP‐TFET: Drain and pocket engineering technique

Abstract: In this article, a Ge-source is employed in split drain Z-shaped line TFET structure (SD-ZHP-TFET) and named as Ge-source SD-ZHP-TFET. The presence of split drain increases the tunnel width at interface of channel-drain, which reduces the ambipolar current (I AMB ). Also, the horizontal pocket at source

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The trap sensitivity for wide range of temperature in presence of acceptor and donor traps of SMG and DMG NRFETs are revealed in figure 10. As temperature rises, the mobility of the charge carriers are degraded, which clues to deprivation in drain current [35]. Thus, maximum trap sensitivity is observed at temperature of 480 K for both acceptor and donor trap.…”
Section: Resultsmentioning
confidence: 99%
“…The trap sensitivity for wide range of temperature in presence of acceptor and donor traps of SMG and DMG NRFETs are revealed in figure 10. As temperature rises, the mobility of the charge carriers are degraded, which clues to deprivation in drain current [35]. Thus, maximum trap sensitivity is observed at temperature of 480 K for both acceptor and donor trap.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the efficiency of CZTSe solar cells is reported as 12.6% under AM 1.5 spectrum [2] and can be reached up to 32.2%, which is very high compared to the reported efficiency [3,4]. So to improve the performance of CZTS solar cell lot of experimental and theoretical studies have been reported so far [5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…Bottom side of gate provides immunity against reverse leakage current in a regular manner. As a result, the simulated device is described as the Z-shape horizontal pocket line TFET analogical to the oxide structure in Z-shape [15][16][17][18][19][20]. A high-k oxide (HfO 2 ) layer is placed over the source area in ZHP TFETs, while a thin film of silicon dioxide (SiO 2 ) is placed on the back side of the gate.…”
Section: Introductionmentioning
confidence: 99%